KONDUKTIVITAS PANAS DAN KOEFISIEN PINDAH PANAS PADA PROSES PENGERINGAN GABAH DENGAN MENGGUNAKAN CABINET DRYER - Rusli, Riska; Jamaluddin P, Jamaluddin P; Yanto, Subari (Jurnal Pendidikan Teknologi Pertanian, 2018)
The purpose of this research is to know the conductivity and coefficient of heat transfer in drying process of gabah (unhulled rice) by using cabinet dryer. This research is a type of experimental research done by drying "gabah" with temperature variations 50OC, 60OC and 70OC while the duration of drying 160 minutes, 170 minutes and 180 minutes. then to know the temperature change during the drying process used thermocouple, while to know the change of  "gabah"  water  level  is  done  by  water  content  test  before  and  after  drying  by  using  ov en  method. The results show that the higher the drying temperature, the "gabah" temperature will be close to the temperature of hot air, while the moisture content the higher the temperature and drying in a long time will cause the "gabah" water content decreases. The value of the  "gabah" conductivity and the heat transfer coefficient of the"gabah" is 0.32 W/m.OC and 31.77 W/m2.OC.